2009
DOI: 10.1029/2008jf001227
|View full text |Cite
|
Sign up to set email alerts
|

Grounding line movement and ice shelf buttressing in marine ice sheets

Abstract: [1] Understanding the dynamics of marine ice sheets is integral to studying the evolution of the Antarctic ice sheet in both the short and long terms. An important component of the dynamics, grounding line migration, has proved difficult to represent in numerical models, and most successful attempts have made use of techniques that are only readily applicable to flow line models. However, to capture the stress transmission involved in another important component, the buttressing of a marine ice sheet by its ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
241
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(248 citation statements)
references
References 51 publications
(129 reference statements)
7
241
0
Order By: Relevance
“…A recent theoretical, glaciological study concluded that ice shelves fringing marine-based ice streams have a major buttressing effect (Goldberg et al, 2009). Therefore, the ice shelf of the ice stream flowing through Belgica Trough may also have delayed post-LGM grounding-line retreat and contributed to the observed slow and prolonged retreat pattern (Fig.…”
Section: History Of Ice-sheet Retreatmentioning
confidence: 99%
“…A recent theoretical, glaciological study concluded that ice shelves fringing marine-based ice streams have a major buttressing effect (Goldberg et al, 2009). Therefore, the ice shelf of the ice stream flowing through Belgica Trough may also have delayed post-LGM grounding-line retreat and contributed to the observed slow and prolonged retreat pattern (Fig.…”
Section: History Of Ice-sheet Retreatmentioning
confidence: 99%
“…Most importantly, the Schoof (2007) formula includes a parameter that represents buttressing from an ice shelf. Buttressing is crucial because it opposes the tendency of the ice to spread and thin at the grounding-line, and can inhibit retreat and augment advance (Goldberg et al, 2009). Again, numerical experiments indicate that the Schoof (2007) formula is accurate in the presence of specified buttressing (Drouet et al, 2013), but it is also true that representing buttressing by a parameter diverts attention from the interplay between flow across the grounding line and the buttressing from an ice shelf.…”
mentioning
confidence: 99%
“…In particular we assume isothermal ice and a spatially uniform basal friction coefficient, conditions that have been used to analyze ice-sheet dynamics in a number of previous studies (e.g., Dupont and Alley, 2005;Goldberg et al, 2009;Gudmundsson et al, 2012;Pattyn et al, 2013;AsayDavis et al, 2015). Neglecting the terms of vertical shearing in the stress balance and accounting for the small thicknessto-length ratio of ice sheets, the SSA represents the relevant dynamics of floating ice shelves and grounded ice streams.…”
Section: Introductionmentioning
confidence: 99%
“…Neglecting the terms of vertical shearing in the stress balance and accounting for the small thicknessto-length ratio of ice sheets, the SSA represents the relevant dynamics of floating ice shelves and grounded ice streams. The capability of numerical SSA models to simulate these regimes that are characterized by fast plug-like flow has been demonstrated in various studies (e.g., Goldberg et al, 2009;Gudmundsson et al, 2012). The SSA can be complemented by the SIA (Huybrechts, 1990;Sato and Greve, 2012) to also include vertical shearing, which is dominant in the more stagnant interior parts of an ice sheet (Bueler and Brown, 2009;Pollard and DeConto, 2012;Thoma et al, 2015), whereas higher-order approximations (Schoof and Hindmarsh, 2010;Larour et al, 2012;Cornford et al, 2015) neglect less stress components in the full Stokes stress balance .…”
Section: Introductionmentioning
confidence: 99%